A Novel Surgical Technique for treatment of Morel-Lavallée Lesion: Endoscopic debridement combined with percutaneous cutaneo-fascial suture. Issue 8 (August 2018) - Liu, Min; Liu, Liangle; Zhou, Xiaosai; Wu, Lifen; Wang, Juncheng; Qi, Li; Cai, Chunyuan
Abstract: Morel-Lavallée lesions are rare, closed degloving soft tissue injuries in which the skin and subcutaneous tissues are traumatic separated from the underlying fascia. There is lack of consensus regarding optimal management of these lesions. After failure of conservative management, operative intervention is imperative. The purpose of this manuscript is to describe a minimally invasive endoscopic method for treatment of Morel-Lavallée Lesions, which achieves the goal of an open surgical debridement.